Quasi-static test study of tunnel with resistance-limiting shock absorption layer in high-intensity seismic - Li, Pinpin; Qiu, Wenge; Lu, Feng; Yang, Qingwen; Chen, Zhenyu; Li, Linlong; Wang, Yi; Gao, Meiben; Deng, Zhiheng (Frontiers in Earth Science, 2023)
The Sichuan-Tibet Railway is faced with risks of active faults, unfavorable geological conditions, high in-situ stress levels, and a high potential for Traditional tunnel seismic measures that can no longer guarantee the safety of tunnel structures in high-intensity earthquake areas. The new shock absorption capacity layer with resistance-limiting is proposed in this paper and the resistance-limiting shock absorption principle. To study the safety of the new anti-shock lining structure, a large-scale quasi-static model test was carried out based on the improved static-dynamic coupling shear force. The test analyzes the response rules of strain, structural internal force, and lining failure form of tunnel lining, taking into consideration three influencing factors including layer layout position, layout density, and tunnel buried depth. The results showed that: 1) Under the action of low-cycle reciprocating shear strain, the failure mode of the shallow buried tunnel is mainly the tensile failure of the arch waist and the failure of the arch waist and the side wall, and the failure mode of the deeply buried tunnel is mainly the compression failure of the arch waist; 2) Compared with the case of no shock absorption layer 2) Compared with the case of no shock absorption layer, the lining tensile stress on the inner side of the arch waist position is significantly reduced. Under the high shear strain (0.20%), the increased tensile stress trend was slowed down on the inner side walls. 3) The main working area of the resistance-limiting layer can effectively improve the lining stress distribution under ground vibration and protects the tensile damage on the arch waist to the side wall. The width and depth of the crack are weakened and the seismic bearing capacity of the width and depth of the crack is weakened and the seismic bearing capacity of the lining structure is greatly strengthened. 4) The lining cracks without the resistance limiting layer develop violently, and the crack at the arch waist runs The lining structure failure mode of the resistance limiting layer arranged at the arch waist is similar to The lining structure failure mode of the resistance limiting layer.